PRACTICAL ALGORITHM OF SHORT-TERMED INTEGRATIVE PSYCHOTHERAPY FOR NEUROTIC ANXIETY DISORDERS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article examines methods and techniques of short-term integrative psychotherapy of anxiety disorders based on the study of evidence-based research. The main targets and stages of psychotherapeutic intervention within the framework of the studied method are formulated. An algorithm for conducting short-term integrative psychotherapy for anxiety disorders (using generalized anxiety disorder as an example) is presented. The degree of evidence for the effectiveness of specific psychotherapeutic methods and the strength of recommendations are indicated.